THE ROLE OF ENDOCRINOLOGY IN THE TREATMENT OF MULTIFOLLICULAR OVARIAN CYSTS - Qosimova Mohlaroyim Bahromjon kizi; Khodjayeva Dilnoza Bobirjon kizi (TADQIQOTLAR, 2026)
Abstract: This article highlights the pivotal role of endocrinology in the treatment of  multifollicular  ovarian  cysts.  The  research  delves  into  the  pathophysiological mechanisms  behind  multifollicular  ovarian  changes,  discussing  the  influence  of hormonal imbalances and endocrine disorders on ovarian function. The article further analyzes  various  therapeutic  approaches  from  an  endocrinological  perspective  and evaluates  their  effectiveness,  emphasizing  the  necessity  of  integrative  and individualized treatment strategies. The importance of early diagnosis, comprehensive hormonal assessment, and collaboration between gynecologists and endocrinologists are also discussed. Key recommendations for advancing clinical practice in managing multifollicular ovarian cysts are provided.